Inadequate health literacy on childhood immunization and its predictors among antenatal mothers - Mohamad Yusof, Nazatul Yusrina; Mohd Zulkefli, Nor Afiah; Ismail, Suriani; Abd Rashid, Mohammad Faid (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Outbreak of vaccine preventable disease still persists despite good coverage of immunization in Malaysia. Health literacy on childhood immunization is one of essential factor for the outbreak to happen. Thus, this study determined the predictors of health literacy on childhood immunization among antenatal mother in Seremban, Negeri Sembilan. Methodology: A cross sectional study was conducted among 424 antenatal women using a cluster sampling approach. Antenatal women who were Malaysian and not illiterate were chosen in this study. A selfadministered, validated and pretested questionnaire was used to collect data on sociodemographic, socio economic, awareness on immunization, utilization of health care services and health literacy on childhood immunization. The data was analyzed using SPSS version 22.0. Chi Square test was used in bivariate analysis and multiple logistic regression was used to determine the predictors of inadequate health literacy on childhood immunization. Result: Out of 362 respondents, 81.2% were inadequate health literacy. The predictors were maternal education (AOR= 2.608, 95% CI 1.477-4.604), parity (AOR= 1.067, 95% CI 1.103-3.876), residential area (AOR= 2.344, 95% CI 1.184-4.641) and utilization of government hospital (AOR= 2.344, 95% CI 1.184-4.641). Conclusion: Accessibility of health education with regard to immunization need to be strengthen among primigravida, low education and those staying in rural area. In addition, health education also needs to emphasize on the individual that is employed and low economic status with underutilization of government hospital. A simplified education material with interesting pictures and using visual aids help illiterate people for better understanding.